2005
DOI: 10.1007/s00402-005-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Does long-term ischemia affect the oxidant status during fracture healing?

Abstract: We conclude that complete acute transient ischemia affects the oxidant status during fracture healing. This effect especially occurs during the ischemic period, inflammation, and callus formation of fracture healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…As in some other clinical trials (Prasad et al 2003), the levels of NO were found to be high especially on the postfracture 7th and 14th days in the present study. These fi ndings show that NO production increases in an signifi cant amount in the 2nd and 3rd weeks of fracture, when the most intense oxidative stress occurs (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The extreme production of NO may cause peroxynitrite-related tissue damage and a consequent disturbance of fracture healing, especially at the 2nd and 3rd weeks following the fracture.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As in some other clinical trials (Prasad et al 2003), the levels of NO were found to be high especially on the postfracture 7th and 14th days in the present study. These fi ndings show that NO production increases in an signifi cant amount in the 2nd and 3rd weeks of fracture, when the most intense oxidative stress occurs (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The extreme production of NO may cause peroxynitrite-related tissue damage and a consequent disturbance of fracture healing, especially at the 2nd and 3rd weeks following the fracture.…”
Section: Discussionmentioning
confidence: 94%
“…Ischemia-reperfusion mechanisms may cause an oxidative stress injury in a fractured extremity. Some studies indicate that oxidative stress occurred especially on the 7th and 14th days after the fracture (Gokturk et al 1995;Prasad et al 2003;Petrovich et al 2004;Yeler et al 2005;Cetinus et al 2005). The common idea in those studies is as follows: the fi rst few days of fracture healing is the ischemia period and no oxidative stress injury occurs during this time.…”
Section: Discussionmentioning
confidence: 99%
“…So they consider that fracture causes oxidative stress like IR injury, and endogenous antioxidant defense systems may be insufficient to overcome the increased oxidative stress during the first month of fracture healing. Cetinus et al [33] reported that oxidative stress occurring from fracture was increased in callus bone tissue by applying IR. In our study; MDA and PCO levels showing oxidative stress was increased in bone tissue significantly after IR.…”
Section: Discussionmentioning
confidence: 98%
“…The increased levels of oxidative enzymes during the Table 4 The descriptive data of the mean values, standard deviations and p values related to kidney histopathology for each group. healing processes can explain the delay of healing observed in the DEXT and MEL groups because free oxygen radicals are known to impair bone healing [46][47][48]. However, NSAIDs affect the bone fracture healing process through the inhibition of both COX and PGs.…”
Section: Discussionmentioning
confidence: 99%